Efforts to Improve Number Recognition Skills by Using Pamsi Media in TA Al Jabbar - Laila Fadhilah; Indriana Martiningsih; Rila Rahma Mulyani; Lead Ming Seng; Fatoumata Sonko (Classroom Experiences, 2025)
This study was carried out because there aren't enough learning resources that pupils are interested in that help kids learn how to identify numbers. This project intends to enhance group A students at TA Al Jabbar Malang's capacity to identify numbers using PAMASI media. This study used the two-cycle classroom action research (CAR) methodology. The planning stage, the execution stage, the observation stage, and the reflection stage made up each cycle. From January 16 through January 27, 2023, this study was carried out. Twelve students from Al Jabbar TA's group A class served as the study subjects. five female scholars and seven male pupils. This research used observation, interviews, and demonstrations to obtain data. The findings demonstrated that learning via PAMASI media improved one's capacity for number recognition. Prior to the deployment of class action, five children had a strong grasp of the capacity to identify numbers in other pupils. The number of pupils that could identify numerals climbed to seven after the first cycle's adoption. The child's capacity for number recognition improved significantly to nine pupils throughout the execution of cycle II.